Solvent‐Enhanced Conformational Flexibility of Cyclic Tetrapeptides. Issue 13 (13th June 2019) - Berger, Nadja; Wollny, Laura J. B.; Sokkar, Pandian; Mittal, Sumit; Mieres‐Perez, Joel; Stoll, Raphael; Sander, Wolfram; Sanchez‐Garcia, Elsa
Abstract: Solvent and temperature can affect the structural properties of cyclic peptides by controlling their flexibility. Here, we investigate two cyclic peptides, featuring beta turns. Using temperature‐dependent NMR and FT‐IR, we observed a pronounced temperature effect on the conformation of the cyclic peptideD‐1 in CHCl3 but a much smaller effect in CH3 CN. Almost no effect was observed for its diastereomerL‐1 within a similar temperature range and using the same solvents. With the aid of Replica Exchange Molecular Dynamics simulations and Quantum Mechanics/Molecular Mechanics calculations, we were able to explain this behavior based on the increased flexibility ofD‐1 (in CHCl3 ) in terms of intramolecular hydrogen bonding. The largest temperature dependence is observed forD ‐1 in CHCl3, while the temperature effect is less pronounced forL‐1 in CHCl3 and for both peptides in CH3 CN. This work provides new insights into the role of the environment and temperature on the conformations of cyclic peptides. Abstract : Tuning tetrapeptide conformation : A multi‐resolution computational approach was used for the interpretation of the temperature‐dependent NMR and FT‐IR spectra of two cyclic tetrapeptides. We found that the combination of three factors: temperature, solvent, and configuration of the amino acid in position 4 allows tuning the conformational preferences of cyclic tetrapeptides, with potential implications for the targeted design of structures with β‐turn motifs.